Sistem Informasi Penyewaan Kos Dengan Fitur Google Maps API - Danendra Khansa Pallas Wahyudi; Soetam Rizky Wicaksono (Politeknik Negeri Cilacap, 2021)
OKOS is an online boarding information system that can make it easier for boarding house seekers to choose the boarding house they want, besides that boarding house owners can also register their boarding house business premises. OKOS was created to meet the needs of boarding house seekers from outside the city to be more helpful in finding a boarding house and boarding house owners who can be helped in promoting their boarding house business. The method used to research the creation of the OKOS is the SDLC waterfall which consists of planning, analysis, design, implementation, testing, and maintenance. The conclusion from making the OKOS information system website is that OKOS can meet the needs of boarding house owners and boarding house seekers because OKOS can be an intermediary between boarding house seekers and boarding house owners even though they are in different cities. In addition, OKOS provides complete information so that boarding house seekers can choose a boarding house based on the type of boarding house, facilities, price, room area, maximum occupants per room, to a map of the boarding location. The suggestion that the author can convey is that there is a need for further research on what things are considered for boarding house seekers to choose the desired or needed boarding house so that it can be considered by boarding house owners or application developers like OKOS to attract the attention of boarding house seekers